OPTIMALISASI PENDAMPINGAN PADA IBU HAMIL DALAM PERSIAPAN PERSALINAN - Hariastuti, Fela Putri; Saraswati, Devi Endah; Rahmawati, Andin Ajeng (Jurnal Humanis ( Jurnal Pengabdian Masyarakat ISTeK ICsada Bojonegoro), 2024)
Preparation for childbirth is something that must be done by every pregnant mother to face the birth of a baby, whether primiparous or multiparous. The preparation required includes material, physical and mental (psychological). Improving birth readiness is an action plan created by the mother, family members and health care providers to improve the health of the mother and fetus. Efforts to increase childbirth readiness are very important both from a physical and psychological perspective, so that the birth runs smoothly and the mother and baby are safe. This plan can include discussions to ensure that the mother receives the necessary care. Having a birth plan can reduce maternal confusion during childbirth, as well as increase the likelihood that the mother will receive appropriate and timely care. The method used in this community service activity is to provide comprehensive assistance to the families being accompanied. Respondents in community service were 10 pregnant women. Community service activities were carried out in Sumberejo Village, Trucuk District, Bojonegoro Regency in June – July 2024 for 6 weeks. In mentoring activities, midwifery care is provided and health education is provided based on the needs of pregnant women. The results of maternal assistance are within normal limits and there is an increase in knowledge after being given health education. With community service in the form of community service, mothers can provide comprehensive care so that they can improve the quality of healthKeywords?: Mentoring, Pregnant women, preparation for childbirth.